At the Heart of Virtue Growth: 'Self-of-virtue' and 'Virtue identity' - Manuel Joaquín Fernández González (Estudios sobre Educación, 2019)
Within a realist Aristotelian paradigm, this paper explores the concepts of ‘self-of-virtue’ and ‘virtue identity’, its correspondent self-concept. Distinguishing the ‘fundamental disposition’ to virtue growth, which defi nes a self-of-virtue, from the particular dispositions of virtues, we conceptualize virtue growth as an ‘integrative’ and ‘open free systemic’ reality based on phronesis-guided action, and we describe the ‘unifi ed moral self of rationally grounded emotions’. We address the radical difference between virtue identity and moral identity, and we propose a processual model for self-of-virtue development, unfolding its pedagogical aspects and suggesting that refocussing on the development of self-of-virtue would help to avoid atomized virtue education.